AL KALIMᾹT AL MUQTARADAH MIN AL LUGAH AL ‘ARABIYYAH ILᾹ AL LUGAH AL INDŪNISIYYAH FĪ IFTITᾹHI AL DUSTŪR AL INDŪNISIY AL‘ ᾹM 1945 - Kastella, Ghazali Abdul Rahman; Matdoan, Muzna Rahmatia; Mustofa, Syaiful; Muhyiddin, Luthfi (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
Loan words were foreign words used by a particular language to fill a linguistic gap, multiplying borrowed words in the target language. In addition to borrowing words from Sanskrit, Spanish, Portuguese, Dutch, and English, the Indonesian language also use many words from Arabic. As part of this research, the researchers attempted to determine which words were borrowed and to investigate the meaning of the Arabic borrowed words in the primary body of the Indonesian Constitution. The method used for this research was the qualitative descriptive method, and the approach used is a librarian and the procedure for data collection. The researcher used written documents and the method to analyze the data. The researcher used the comparative approach to define the change of meaning of Arabic borrowed words in the Indonesian language in the preamble of the Indonesian Constitution in 1945. The result of the research was the number of Arabic borrowed words at the opening of the Basic Constitution 19. The borrowed word the research is expected to add ınsıght and knowledge ın the field of langueage and can provıde ınformatıon and ınput.